Review and framework for the engineering of Business Models for Sustainability: A System of Systems perspective - Dormeier, Christopher; Mindt, Nadja; Niemeyer, Jan Felix; Asghari, Reza; Mennenga, Mark (Sustainable production and consumption, 2024)
Scarce resources and climate change require more sustainable production and consumption. Business Models for Sustainability (BMfS) can be crucial in achieving extended life cycles and a more conscious use of materials. Due to the high interdependence and interconnectedness of different BMfS compared with traditional business models, the application of conventional approaches for the design of BMfS is limited. Therefore, we show that a systemic perspective is required to achieve absolute sustainability that transcends the boundaries of a focal company. We then conduct a two-part systematic literature review focusing on existing approaches to support a systemic perspective in the design and analysis of BMfS first and modeling approaches second. Based on this review, we identify seven general approaches to achieve a more systemic perspective and six types of approaches to modeling BMfS. We further derive ten key findings and 36 requirements for a framework for the engineering of BMfS. Based on this, we introduce a System of Systems (SoS) perspective on BMfS to enable the required systemic perspective and propose a framework for the engineering of a system of BMfS (SoBMfS) providing a systematic multi-perspective, multi-level approach bridging micro-, meso-, and macro-level. Scholars and practitioners can use this framework to develop and integrate future tools and methods to support the development of BMfS. [Display omitted]